Targeting Pin1 by inhibitor API‐1 regulates microRNA biogenesis and suppresses hepatocellular carcinoma development. Issue 2 (21st May 2018) - Pu, Wenchen; Li, Jiao; Zheng, Yuanyuan; Shen, Xianyan; Fan, Xin; Zhou, Jian‐Kang; He, Juan; Deng, Yulan; Liu, Xuesha; Wang, Chun; Yang, Shengyong; Chen, Qiang; et al.
Abstract : Hepatocellular carcinoma (HCC) is a leading cause of cancer death worldwide, but there are few effective treatments. Aberrant microRNA (miRNA) biogenesis is correlated with HCC development. We previously demonstrated that peptidyl‐prolyl cis ‐ trans isomerase NIMA‐interacting 1 (Pin1) participates in miRNA biogenesis and is a potential HCC treatment target. However, how Pin1 modulates miRNA biogenesis remains obscure. Here, we present in vivo evidence that Pin1 overexpression is directly linked to the development of HCC. Administration with the Pin1 inhibitor (API‐1), a specific small molecule targeting Pin1 peptidyl‐prolyl isomerase domain and inhibiting Pin1 cis ‐ trans isomerizing activity, suppresses in vitro cell proliferation and migration of HCC cells. But API‐1‐induced Pin1 inhibition is insensitive to HCC cells with low Pin1 expression and/or low exportin‐5 (XPO5) phosphorylation. Mechanistically, Pin1 recognizes and isomerizes the phosphorylated serine‐proline motif of phosphorylated XPO5 and passivates phosphorylated XPO5. Pin1 inhibition by API‐1 maintains the active conformation of phosphorylated XPO5 and restores XPO5‐driven precursor miRNA nuclear‐to‐cytoplasm export, activating anticancer miRNA biogenesis and leading to both in vitro HCC suppression and HCC suppression in xenograft mice. Conclusion : Experimental evidence suggests that Pin1 inhibition by API‐1 up‐regulates miRNA biogenesis by retaining active XPO5 conformation and suppresses HCC development, revealing the mechanism of Pin1‐mediated miRNA biogenesis and unequivocally supporting API‐1 as a drug candidate for HCC therapy, especially for Pin1‐overexpressing, extracellular signal–regulated kinase–activated HCC. (Hepatology 2018).